Adherence to stress-related mucosal damage prophylaxis guideline in patients admitted to the Intensive Care Unit - Niloofar Rafinazari; Saeed Abbasi; Shadi Farsaei; Marjan Mansourian; Peyman Adibi (Wolters Kluwer Medknow Publications, 2016)
Objective: Concern about adverse effects of the inconsistent use of stress-related mucosal damage prophylaxis in intensive care unit (ICU) is increasing. Hence, this study was designed to prospectively evaluate the rate of inappropriate stress ulcer prophylaxis (SUP) administration upon ICU admission, at ICU discharge and determine the adherence to American Society of Health-System Pharmacists (ASHP) guideline during ICU stay. Methods: In this study, 200 patients were randomly selected from all ICU admissions during 9 months. Risk factors of stress ulcer were recorded daily during ICU stay and appropriateness of SUP administration was assessed according to the ASHP criteria. Findings: Of all 160 (80%) patients who received SUP, 44.4% did not have indication; and among 95 patients with an indication for SUP administration, 6.3% did not receive it upon ICU admission. Consequently, 77 (38.5%) of 200 patients received inappropriate prophylaxis on ICU admission. In addition, 53.5% of patients had appropriate adherence to ASHP guideline during all days of ICU stay (44% and 2.5% of patients received SUP more than 120% and <80% of appropriate SUP duration, respectively). Moreover, 81.2% were continued on inappropriate prophylaxis upon transfer from the ICU. Conclusion: We concluded that although SUP administration included both overutilization and underutilization in this ICU, but high prevalence of SUP overutilization caused unnecessary hospital costs, personal monetary burden, and may increase adverse drug reactions. Therefore, educating physicians and cooperation of clinical pharmacists regarding implementing standard protocols could improve patterns of SUP administration.